Amplitude‐integrated electroencephalography shows that doxapram influences the brain activity of preterm infants. (27th May 2014) - Czaba‐Hnizdo, Christine; Olischar, Monika; Rona, Zsofia; Weninger, Manfred; Berger, Angelika; Klebermass‐Schrehof, Katrin
Abstract Aim The aim of this study was to measure the brain activity of preterm infants treated with caffeine citrate and doxapram for preterm apnoea, using amplitude‐integrated electroencephalography (aEEG), to identify any adverse effects on cerebral function. Methods We analysed the aEEG tracings of 13 preterm infants <30 weeks of gestation before, during and after doxapram treatment, with regard to background activity (percentages of continuous and discontinuous patterns), occurrence of sleep‐wake cycling and appearance of electrographic seizure activity. They were also compared with 61 controls without doxapram treatment. Results During doxapram treatment, aEEG tracings showed an increase in continuous background activity (19 ± 30% before treatment, 38 ± 35% during treatment) and a decrease in discontinuous patterns. In addition, they showed more frequent electrographic seizure activity (0% before treatment, 15 ± 37% during treatment) and less frequent sleep‐wake cycling (92 ± 27% before treatment, 85 ± 37% during treatment) could be observed. These results were confirmed when compared to the control group. Conclusion Doxapram treatment influences aEEG in preterm infants, showing higher percentages of continuous activity as well as more electrographic seizure activity and less sleep‐wake cycling. It should, therefore, be used with caution in very preterm infants.